A generic realignment of the Oncocnemidini sensu Hodges (1983) (Lepidoptera: Noctuidae: Oncocnemidinae), with description of a new genus and 50 new species - Troubridge, J. T. (Zootaxa, 2008)
The former genera Oncocnemis Lederer, Apharetra Grote, Hemistilbia Barnes and Benjamin, Adita Grote, Lepipolys Guenée, Homoncocnemis Hampson, and Homohadena Grote are synonymized under Sympistis Hübner. The following are transferred from Oxycnemis Grote to Sympistis: Sympistis franclemonti (Blanchard), comb. n. [Oxycnemis franclemonti Blanchard] and Sympistis subsimplex (Dyar) comb. n. [Oxycnemis subsimplex Dyar]. Two species are transferred to Unciella gen. n. as Unciella primula (Barnes and McDunnough) comb. n. [Oncocnemis primula Barnes and McDunnough] and Unciella flagrantis (Smith) comb. n. [Oncocnemis flagrantis Smith], which along with Leucocnemis Hampson are transferred to tribe Triocnemidini in the Psaphidinae. Supralathosea Barnes and Benjamin is transferred to Psaphidinae: Psaphidini and Catabena pronuba Barnes and McDunnough is transferred to Supralathosea comb. n.. In addition, Cerapoda Smith syn. n. and Prochloridea Barnes and McDunnough syn. n. (Prochloridea is presently in Hodges “unassociated genera”) are synonymized under Rhizagrotis Smith in the Xyleninae. Copanarta sexpunctata Barnes and McDunnough rev. comb. is transferred from Stylopoda to Copanarta. Oncocnemis simplicia Smith syn. n. is synonymized under Homohadena deserta Smith, Oncocnemis mus Troubridge and Crabo syn. n. under Oncocnemis tenuifascia Smith, and Oncocnemis sala Mustelin syn. n. under Oncocnemis aqualis Grote. The following are elevated to species rank: Sympistis deserticola (McDunnough) stat. n., comb. n. [Oncocnemis riparia deserticola McDunnough], Sympistis pallidior (Barnes) stat. n., comb. n. [Oncocnemis figurata pallidior Barnes] and Sympistis pallida (Barnes) stat. n., comb. n. [Oncocnemis homogena pallida Barnes]. The following 50 species are described as new: Sympistis acheron Troubridge, Sympistis amenthes Troubridge, Sympistis amun Troubridge, Sympistis anubis Troubridge, Sympistis anweileri Troubridge and Lafontaine, Sympistis apep Troubridge, Sympistis apis Troubridge, Sympistis babi Troubridge, Sympistis baloghi Troubridge, Sympistis bes Troubridge, Sympistis buchis Troubridge, Sympistis buto Troubridge, Sympistis cherti Troubridge, Sympistis chons Troubridge, Sympistis cleopatra Troubridge, Sympistis cocytus Troubridge, Sympistis collaris Troubridge, Sympistis dischorda Troubridge, Sympistis disfigurata Troubridge, Sympistis doris Dimock and Troubridge, Sympistis hapi Troubridge, Sympistis hathor Troubridge, Sympistis horus Troubridge, Sympistis incubus Troubridge, Sympistis insanina Troubridge, Sympistis isis Troubridge, Sympistis jenniferae Troubridge, Sympistis jocelynae Troubridge, Sympistis khem Troubridge, Sympistis khepri Troubridge, Sympistis knudsoni Troubridge, Sympistis lachrymosa Troubridge, Sympistis min Troubridge, Sympistis mut Troubridge, Sympistis nenun Troubridge, Sympistis opleri Troubridge, Sympistis osiris Troubridge, Sympistis pachet Troubridge, Sympistis ptah Troubridge, Sympistis ra Troubridge, Sympistis richersi Troubridge, Sympistis sakhmet Troubridge, Sympistis septu Troubridge, Sympistis sesmu Troubridge, Sympistis seth Troubridge, Sympistis shait Troubridge, Sympistis shirleyae Troubridge, Sympistis sobek Troubridge, Sympistis sokar Troubridge, and Sympistis serapis Troubridge. Color illustrations are provided for adults of all nearctic Sympistis species. Alphabetical and phylogenetic checklists of North American Oncocnemidinae are also provided, including species formerly placed there, but here transferred to other subfamilies.